2014
DOI: 10.1177/2045125314553612
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between total vitamin D levels and psychotic psychopathology in patients with schizophrenia: therapeutic implications for add-on vitamin D augmentation

Abstract: Even though important factors for vitamin D synthesis were similar, there was severe vitamin D deficiency in patients presenting with an acute episode, significantly different from those in remission. Is vitamin D deficiency the result or the cause of an acute episode? Our results contribute to the idea that vitamin D deficiency and schizophrenia may have interactions with an unknown pathway. Present data points out a possible influence at a genomic level. Future trials may investigate this association with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 21 publications
6
47
1
2
Order By: Relevance
“…This high proportion of patients with low S-25 OH D is of importance since this might influence morbidity both related to depressive (Berg et al, 2010), positive (Yuksel et al, 2014), negative (Graham et al, 2014) or atypical symptoms (Dealberto, 2013). There were no significant correlations between S-25 OH D and positive or negative symptomatology in the current study, but there was a moderate association between low S-25 OH D and increased depressive symptomatology in the FEP group.…”
Section: Discussioncontrasting
confidence: 61%
“…This high proportion of patients with low S-25 OH D is of importance since this might influence morbidity both related to depressive (Berg et al, 2010), positive (Yuksel et al, 2014), negative (Graham et al, 2014) or atypical symptoms (Dealberto, 2013). There were no significant correlations between S-25 OH D and positive or negative symptomatology in the current study, but there was a moderate association between low S-25 OH D and increased depressive symptomatology in the FEP group.…”
Section: Discussioncontrasting
confidence: 61%
“…In fact, Lebanon is located at appropriate latitudes (33° 35'N) [38] for the synthesis of vitamin D [39] and thus, higher levels of total vitamin D would be expected [39]. Furthermore, our results indicated that patients with schizophrenia, as well as the healthy ones, had a vitamin D deficiency, similar to previous studies [2,4,36,37,40,41]. Other studies conducted in Lebanon had shown a hypovitaminosis D in the healthy population [35,[42][43][44][45].…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, low serum vitamin D levels, correlating with the severity of phsychotic symptoms, have been found in SZ patients [Yüksel et al, 2014]. The molecular background of this link may rely on shared features of latitude adaptation observed in both SZ-and vitamin D-related genes, suggesting that SZ etiopathogenesis may encounter latitudedependent adaptive changes in vitamin D metabolism [Amato et al, 2010].…”
Section: Other Featuresmentioning
confidence: 99%